Pengembangan Bahan Ajar Bermuatan Pendidikan Karakter - Hartati, Tri Asih Wahyu; Saputro, Yulianto Dwi; Pangestuti, Ardian Anjar; Budijanto, Budijanto (FKIP Universitas Wisnuwardhana, 2021)
The purpose of this development research is to produce teaching materials containing character education for the Learning Design and Strategy courses. This research method is development research using the 4D model which consists of the stages of define, design, develop, and dissemination. The research subjects were class B students of class 2017 in the 2017/2018 academic year. Data collection was carried out by interviewing lecturers and students and distributing questionnaires. The data were analyzed by using quantitative descriptive analysis. The result of this research is the availability of design teaching materials and learning strategies with characters that have been valid and implemented at IKIP Budi Utomo. Based on the results of the validation of teaching materials by media experts, material experts, and linguists, it can be concluded that the teaching materials are suitable for use in learning.